PELATIHAN MENGGUNAKAN DIGITAL MARKETING UNTUK MEMASARKAN PRODUK UMKM PENGRAJIN TAS LOKAL CHESSY, DESA TEGALWARU KABUPATEN BOGOR - Dwi Mandasari Rahayu; Yuyun Khairunisa (Jurnal Abdi Insani, 2023)
The Covid-19 pandemic situation affected the state of the economy, many companies were "laying off" their workers to cover losses. This situation underlies the establishment of the Chessy Local Bag UMKM in Tegal Waru District, Bogor Regency. Based on the results of interviews with Chessy Local Bag Craftsmen MSME owners that there have been problems so far using conventional marketing. This resulted in marketing that was carried out less than optimally so that the products sold experienced stagnation and even delays. The purpose of this activity is to increase the knowledge and skills of employees at UMKM Chessy Local Bags using Digital Marketing. The implementation method uses a qualitative approach. Activities are divided into six stages, namely; preparation, data collection, implementation, evaluation, preparation of results, and reporting of implementation results. The data collection techniques used are: interviews, questionnaires, observation and literature study. As for the survey results on the activity, namely that there were 66.67% of respondents who did not understand digital marketing at all after attending the training, they understood, 100% of respondents said that digital marketing training carried out in this activity could increase understanding. There are several types of digital marketing that have been explained and 100% of respondents are most comfortable using the marketplace to market their products because it can affect sales. The implementation of community service went smoothly, the participants enthusiastically participated in the series of activities until they were finished. Participants hope that more training will be held with different topics for Chessy Local Tas UMKM employees. The conclusion from this activity is that the training carried out can increase the knowledge and skills of Chessy Local Tas UMKM employees to use Digital Marketing.